Mapping motivation for top performing teams - Sale, James (Motivational speaker) (Complete guide to mapping motivation., 2021)
"Mapping Motivation for Top Performing Teams is the final in a series of books that are all linked to the author's Motivational Map toolkit. Each book builds on a different aspect of personal, team and organisational development. This book, using the Motivational Map, the Team Motivational Map, as well as the Organisation Motivational Map, is a practical guide to understanding how team dynamics and success are hugely influenced by motivational factors, which are not usually taken into account. The book is a deeper exploration of team mapping which occurs in: chapter 6 of Mapping Motivation (Gower, 2015), chapter 6 of Mapping Motivation for Engagement (with Steve Jones, Routledge, 2019), and chapter 6 Mapping Motivation for Leadership (with Jane Thomas, Routledge, 2020). But whereas these chapters only touched on specific aspects of team dynamics, this book covers the issues more comprehensively; it also attempts to avoid replication of materials, although there are bound to be small overlaps. It covers not only how motivations affect team productivity and how this can be boosted through targeted Reward Strategies, but also how 'mapping' provides profounder insights into the four key characteristics of top performing teams: the clear remit, vital interdependency, strong belief, and real accountability. How Motivational Maps covers these areas, we believe to be original, eye-opening and effective in the management of change. Further, as always with Motivational Maps, its language and metrics raise self-awareness at an individual and team level, and so can help resolve conflicts through its common and non-judgmental language. Managing teams is the key skill of managers: thus this book is a handbook for managers everywhere who wish to excel at management, for without bringing their teams on board (i.e. motivating their teams), they are not effectively managing"--